Comparing Logistic Support and Race Organization and their Effect on Psychological Toughness of National Center for Gifted in Sports Players and League Club players - Hamad, Faraj; Diaa , Duraid; Gafel , Taha (Journal of Physical Education, 2023)
The research aimed at comparing logistic support and race organization and their effect on psychological toughness of national center for gifted in sports players and league club players. The subjects were (22) players from different sport institutions and the researchers applied Sameer Sabri Hassan’s psychological toughness scale 2020. The scale consisted of (29) item to conclude that training and competition as well as other stress led to exhausting the players energy sources and negatively affect this thinking. In addition to that, the researchers concluded that continuous change in life and its variables and commitments create great psychological stress on the players and all those surrounding them. Finally, they concluded that logistic support and increased participations lead to increased psychological toughness in players.